The introduction of ceramics in the Ertebølle Culture - Poulsen, Karen (Danish Journal of Archaeology, 2013)
Pottery production has long been viewed as an integrated part of the Neolithic package. Instances of ceramic production in hunter-gatherer contexts have been explained by influences from early farmers. This has also been the case for the ceramics of the Ertebølle Culture. Recently, however, the discussion has become more nuanced and alternative explanations have emerged. This article argues that a focus on the life cycle of the early ceramics as well as an understanding of technology transfer as a process of cultural transmission can potentially broaden the perspective on the uptake of ceramics technology by the hunter-gatherers of northern Europe. The chaîne opératoire of the Ertebølle ceramics is analysed and a model of how a technology moves from one social setting to another is presented. In the light of this work, different approaches to the introduction of ceramics in the western Baltic are discussed. It is argued that important elements of the Ertebølle pottery tradition came from the east via Baltic exchange networks. However, the tradition was not directly transferred, and important elements appear along the way. Whether some of these elements can be ascribed to agro-pastoralist groups in the south is still uncertain.